Postoperative pain therapy with hydromorphone; comparison of patient-controlled analgesia with target-controlled infusion and standard patient-controlled analgesia A randomised controlled trial - Wehrfritz, Andreas; Ihmsen, Harald; Fuchte, Tobias; Kim, Michael; Kremer, Sven; Weiss, Alexander; Schüttler, Jürgen; Jeleazcov, Christian (European Journal of Anaesthesiology, 2020)
BACKGROUND The challenge of managing acute postoperative pain is the well tolerated and effective administration of analgesics with a minimum of side effects. The standard therapeutic approach is patient-controlled analgesia (PCA) with systemic opioids. To overcome problems of oscillating opioid concentrations, we studied patient-controlled analgesia by target-controlled infusion (TCI-PCA) as an alternative. OBJECTIVE To compare efficacy, safety and side effects of standard PCA with TCI-PCA for postoperative pain therapy with hydromorphone. DESIGN Single-blinded, randomised trial. SETTING University Hospital, Germany from December 2013 to April 2015. PARTICIPANTS Fifty adults undergoing cardiac surgery. INTERVENTIONS Postoperative pain therapy on the ICU was managed with intravenous (i.v.) hydromorphone and patients randomised to TCI-PCA with target plasma concentrations between 0.8 and 10 ng ml(-1), or PCA with bolus doses of 0.2 mg. Pain was regularly assessed using the 11-point numerical rating scale (NRS). Blood pressure, heart rate, oxygen saturation and cardiac output were continuously monitored, and adverse events were registered throughout the study. MAIN OUTCOME MEASURES NRS pain ratings, hydromorphone doses, haemodynamic effects and side effects. RESULTS NRS pain ratings, total doses of hydromorphone and haemodynamic data did not differ significantly between TCI-PCA and PCA. The number of bolus doses during PCA was significantly higher than the number of target increases during TCI-PCA (P = 0.006). The number of negative requests was also significantly higher during PCA than during TCI-PCA (P = 0.02). The respiratory rate on the first postoperative morning was 25 +/- 6 min(-1) during TCI-PCA, compared with 19 +/- 4 min(-1) during PCA (P = 0.022). Nausea occurred in 30% after TCI-PCA and 24% after PCA (P = 0.46). CONCLUSION TCI-PCA was effective and well tolerated in acute postoperative pain management after cardiac surgery. Further studies are needed to evaluate this approach in clinical practice.
CRIS-Team WoS Importer:2020-11-27